Reformasi Birokrasi dan Merit Sistem Pemerintahan Daerah (Studi Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Di Kabupaten Lamongan) - Fahmi Anas; Shodikin Shodikin (Universitas Islam Darul Ulum Lamongan, 2025)
Human Resource Management must always be related to the goals and objectives of the organization (strategic alignment), Human Resource Management or ASN is carried out to motivate and also increase employee productivity in carrying out their duties so that they are able to contribute to achieving the goals and objectives of the Agency. The Research Design uses a qualitative approach. The results of the study illustrate that the development of apparatus resources needs to be focused on developing several things, namely: skills and expertise; insight and knowledge; talent and potential; personality and work motives; and morals and work ethic. Merit-based human resource management is believed to be able to attract the best people to work in an Agency. Lamongan Regent Regulation Number 18 of 2021 concerning the awarding of ASN awards is a real form of concern from the Government through the Lamongan Regency BKPSDM. the issuance of the Perbup regarding the awarding of awards is to increase the spirit of devotion as ASN, increase motivation and work enthusiasm in carrying out main tasks, increase ASN productivity performance, improve the quality of integrity in work and encourage exemplary values in work.